Comparative characterization of aggregates obtained from igneous rocks used in road construction - Chiman, Alexei (2025)
The performance of mineral aggregates in road construction asphalt mixtures, specifically depends on a complex interaction of factors including geological component (rock type, and general mineralogical variation of mineral material) will be reflected in the physical and mechanical properties for use, such as mechanical strength, durability and performance, among others. The analysis of aggregates, mostly focus on the evaluation and correlation of physical properties that define their competition and shown little interest in improving the prediction of the integral behavior of mineral material. In this sense, as a contribution to get an estimate on comparative characterization of aggregates then assessing some geological and mechanical aggregate properties from igneous rocks, and correlations among themselves and with some particular mineralogical characteristics is presented.